Serum lipid profile and retinol in rats fed micronutrient rich edible vegetable oil blend - HAMID NAWAZ KHAN; HUMAIRA FAROOQI; SHAKIR ALI; JAFAR S. KHAN (Smujo International, 2010)
Abstract. Khan HN, Farooqi H, Ali S, Khan JS. 2010. Serum lipid profile and retinol in rats fed micronutrient-rich edible vegetable oil blend. Nusantara Bioscience 2: 109-116. The animal rats were given 10% oil mixed in fat-free diet for one month or six months. In the experiment, the groups of rats were fed with the micronutrient (MN) rich blends mixed previously with 1% cholesterol, and their effects were tested on serum lipid profile. Most significant changes in the High Density Lipoprotein (HDL) cholesterol were observed in one-month study where HDL increased from 24 mg/dl in group to 64 mg/dl in the Mustard palm olein oil blend (MP); in mustard oil (MO) alone fed rats, the HDL was 36 mg/dl. Serum retinol was analyzed as one of the important MN in rats receiving the diet mixed with the blend for various duration of time. The results assume great significance as MO or palm olein oil (PO) alone could not bring the maximum beneficial effects, and the blends appear to have more merit as healthy oils in alleviating adverse health condition such as coronary heart disease (CHD), diabetes, obesity, and hypertension.